Air rescue teams - Green, Michael 1952- (Mankato, MN : Capstone Books, 2000)
Presents information about air rescue teams including their history, aircraft and equipment, training, and plans for the future.
Includes bibliographical references (p. 46) and index.
Keywords: Search and rescue operations -- Juvenile literature; Rescue work -- Juvenile literature; Rescue work